2006
DOI: 10.1002/jcp.20955
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell response to lactate: Implication of PAR modification of VEGF

Abstract: Angiogenesis, the process of formation of new blood vessels from pre-existing one, occurs in many physiological and pathological conditions, most of which are underlined by hypoxia and resultant accumulation of lactate. Although lactate is known to induce angiogenesis, the mechanism of its action on endothelial cells (ECs) is not known. The present study was designed to examine the response of ECs to lactate. Morphological analysis revealed that human umbilical vein endothelial cells (HUVECs) in culture respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 55 publications
4
100
0
Order By: Relevance
“…Endothelial cells and macrophages increase VEGF synthesis when incubated in the presence of lactate (8,30). The data from siRNA experiments and those with HIF-1 null mice indicate that the augmented synthesis of growth factors in lactate-supplemented Matrigel was due to HIF-1 (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Endothelial cells and macrophages increase VEGF synthesis when incubated in the presence of lactate (8,30). The data from siRNA experiments and those with HIF-1 null mice indicate that the augmented synthesis of growth factors in lactate-supplemented Matrigel was due to HIF-1 (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Lactate was previously documented to stimulate angiogenesis (14-16) through activation of the VEGF/VEGFR2 signaling pathway (16)(17)(18)(19)(20). Although it may be difficult to discriminate between the role of hypoxia and lactate in triggering VEGF signaling in vivo, our finding of NF-kB acting as a lactate-responsive transcription factor unravels a pathway which may link tumor cell metabolism and angiogenesis independently of the O 2 conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, high lactate levels were found to be associated with a high incidence of distant metastases already in early stages of the disease and inversely, longer survival was associated with low lactate concentrations in tumors. Among the possible mechanisms supporting these clinical data, lactate is proposed to stimulate angiogenesis (14)(15)(16)(17) through an activation of the VEGF/VEGFR2 signaling pathway (18)(19)(20); a parallel lactate-induced TGFb-1-mediated pathway was also proposed to prevent maturation of neoformed tubes (21). Because of the known HIF-mediated regulation of VEGF (22) and the capacity of glycolytic carboxylate intermediates including pyruvate and lactate to stimulate hypoxia-inducible factor (HIF) expression (23,24), the effects of lactate on VEGF (and angiogenesis in general) are thought to be HIF-1a-dependent (16).…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic nature of the glycolytic inhibition has to be cautiously addressed since, using that as a therapeutic strategy would inflict serious harm to highly glycolytic organs such as brain etc. [16]. Further 2-DG at higher concentrations has also been reported to elicit unfolded protein response (UPR) [17].…”
mentioning
confidence: 99%
“…The angiogenic potency has been reported to be reduced due to a decrease in the production and secretion of VEGF as well as through the mechanism that regulate poly ADP ribosylation of VEGF and thereby making it biologically less active [21]. It is reported that transcriptional coactivator PGC-1α stimulates angiogenesis by inducing VEGF expression through interacting with estrogen-related receptor-α (ERR-α), thereby preparing the tissue for oxidative metabolism [22]. The two important transcriptional factors which regulate the expression of VEGF in response to metabolic changes are, HIF and FOXO [23].…”
mentioning
confidence: 99%